Leaves of grass - Whitman, Walt, 1819-1892 (Floating Press, 2008)
Leaves of Grass is a collection of poems by Walt Whitman originally published in 1855 at the poet's own expense. Criticized when first released for Whitman's use of free verse and his rather racy depictions of sexual love and the senses, Leaves of Grass is a celebration of the human form, the material world and nature.